RANCANG BANGUN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN SIMULASI DIGITAL DI SMK - Syawaluddin Syawaluddin; Elfi Tasrif (Universitas Negeri Padang, 2019)
Today the use of interactive media to support the learning system so that there is an increase in students towards learning outcomes. Technical in implementing learning media can involve almost all the senses of students. Because the media that has been designed is one of the new learning innovations, combined in it there are videos, images, sounds, and other aspects that support to explain the material so that students are easy to take part in learning. In this design there are several elements that are combined including images, animation, sound, and navigation buttons to facilitate users in using interactive media, this interactive multimedia learning media designed with an attractive appearance is presented in interactive CD so students can learn learning material independently. Keywords: Designing, Interactive Media Learning.